ANALISIS DINAMIKA KELOMPOK TANI NELAYAN DI PESISIR KOTA BONTANG - Gusti Haqiqiansyah (Agriekonomika, 2016)
This purpose of research is to assess the level of dynamics farmer group of fishermen at Coastal in Bontang. Collected  data with survey methods, namely direct observation and interviews with respondents. Respondents were taken as many as 30 people who are members of farmer groups of fishermen. The data obtained were processed, tabulated and analyzed descriptively and using scoring techniques. The results showed that from the aspect of group dynamics analysis that the scores achieved relatively high, with the average score achieved by 89.85 (scores range from 75.1 to 97.5) .This suggests that groups of fishermen are relatively dynamic, meaning fellow members of farmers fishermen able to foster good cooperation.